Ortervirales: new virus order unifying five families of reverse-transcribing viruses - Krupovic, M.; Blomberg, J.; Coffin, J.M.; Dasgupta, I.; Fan, H.; Geering, A.D.; Gifford, R.; Harrach, B.; Hull, R.; Johnson, W.; Kreuze, Jan F.; Lindemann, D.; et al. (American Society for Microbiology, 2018)
Reverse-transcribing viruses, which synthesize a copy of genomic DNA from an RNA template, are widespread in animals, plants, algae, and fungi. This broad distribution suggests the ancient origin(s) of these viruses, possibly concomitant with the emergence of eukaryotes. Reverse-transcribing viruses include prominent human pathogens, such as human immunodeficiency viruses 1 and 2 (HIV-1/2) and hepatitis B virus, as well as plant pathogens that cause considerable economic losses.